Nuclear defects in skeletal muscle from a Dynamin 2-linked centronuclear myopathy mouse model - Fongy, Anaïs (Sci Rep, 2019)
Dynamin 2 (DNM2) is a key protein of the endocytosis and intracellular membrane trafficking machinery. Mutations in the DNM2 gene cause autosomal dominant centronuclear myopathy (CNM) and a knock-in mouse model expressing the most frequent human DNM2 mutation in CNM (Knock In-Dnm2(R465W/+)) develops a myopathy sharing similarities with human disease. Using isolated muscle fibres from Knock In-Dnm2(R465W/+) mice, we investigated number, spatial distribution and morphology of myonuclei. We showed a reduction of nuclear number from 20 weeks of age in Tibialis anterior muscle from heterozygous mice. This reduction is associated with a decrease in the satellite cell content in heterozygous muscles. The concomitant reduction of myonuclei number and cross-section area in the heterozygous fibres contributes to largely maintain myonuclear density and volume of myonuclear domain. Moreover, we identified signs of impaired spatial nuclear distribution including alteration of distance from myonuclei to their nearest neighbours and change in orientation of the nuclei. This study highlights reduction of number of myonuclei, a key regulator of the myofiber size, as a new pathomechanism underlying muscle atrophy in the dominant centronuclear myopathy. In addition, this study opens a new line of investigation which could prove particularly important on satellite cells in dominant centronuclear myopathy.